An investigation of the tensile characteristics of printed handsheets - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The purpose of this paper is to investigate the influences of fibre lengths and a given range of paper grammages on the fundamental properties of unprinted and printed papers by using mineral oil-based offset printing inks and also evaluate these results in terms of printing and tensile characteristics. Design/methodology/approach A design research approach has been based on the production of various laboratory handmade papers and their printing process with mineral oil-based offset printing inks. The analysis of mechanical and structural tests results of the unprinted and the printed papers have been evaluated. Findings This study is confirmed that the mineral oil-based offset printing inks can be easily applied to the surface of papers having different grammages and pulp contents. An increase was observed in the tensile index values of the papers with the printing process, and these increases were more evident (about 80%) particularly in low grammage papers having high short fibre content. Originality/value The originality of this work is based on understanding and comparing the effects of grammage and the effect of pulp contents (having long and short fibre) on tensile characteristics of printed and unprinted handsheets.
Keywords: Fibre length; Grammage; Handsheets; Printing effects; Tensile characteristics; COATING STRUCTURE; SURFACE-ROUGHNESS; CELLULOSIC FIBERS; BASE PAPER; WET WEBS; STRENGTH; GRAMMAGE; GLOSS; LENGTH; PULP